2012
DOI: 10.4037/ajcc2012301
|View full text |Cite
|
Sign up to set email alerts
|

Sedation in Adults Receiving Mechanical Ventilation: Physiological and Comfort Outcomes

Abstract: Objective To describe the relationships among sedation, stability in physiological status, and comfort during a 24-hour period in patients receiving mechanical ventilation. Methods Data from 169 patients monitored continuously for 24 hours were recorded at least every 12 seconds, including sedation levels, physiological status (heart rate, respiratory rate, oxygen saturation by pulse oximetry), and comfort (movement of arms and legs as measured by actigraphy). Generalized linear mixed-effect models were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 46 publications
2
21
0
1
Order By: Relevance
“…[52] These findings suggest a widespread culture of keeping mechanically ventilated ICU patients at deep levels of sedation in order to facilitate ICU patient care activities. The results of the current study are in agreement with Payen et al (2007) [2] who found that 41% to 57% of assessed patients were in a deep sedation state and Grap et al (2012) [53] who observed that patients spent 80% of the time in mild/deep sedation and only 20% awake/alert. It was found during the present study that all patients experienced pain all over the study period and the pain score was remained within moderate level using CPOT.…”
Section: Discussionsupporting
confidence: 82%
“…[52] These findings suggest a widespread culture of keeping mechanically ventilated ICU patients at deep levels of sedation in order to facilitate ICU patient care activities. The results of the current study are in agreement with Payen et al (2007) [2] who found that 41% to 57% of assessed patients were in a deep sedation state and Grap et al (2012) [53] who observed that patients spent 80% of the time in mild/deep sedation and only 20% awake/alert. It was found during the present study that all patients experienced pain all over the study period and the pain score was remained within moderate level using CPOT.…”
Section: Discussionsupporting
confidence: 82%
“…Sedation is inherently associated with mechanical ventilation. Grap and colleagues 16 investigated the relationships among sedation, stability in physiological status, and comfort as assessed by using actigraphy to measure limb movement. Level of sedation did not influence physiological measures, but actigraphy findings differed with depth of sedation, reflecting higher comfort levels in deeply sedated patients.…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…Furthermore, the role of activation of afferent fibers of the autonomic nervous system could be explored in experiments with pharmacological or surgical manipulations of the noradrenergic and vagus systems. Grap et al 26 had suggested that the level of sedation most likely does not affect the stability of physiological status but does have an effect on comfort. However, we cannot provide explanations for the data on severity of patients measured with APACHE and need of mechanical ventilation and sedation.…”
Section: Discussionmentioning
confidence: 99%